Absorption capacity of fructose in healthy adults. Comparison with sucrose and its constituent monosaccharides. Issue 10 (October 1986) - Rumessen, J J; Gudmand-Høyer, E
Abstract : The capacity to absorb fructose in 10 healthy adults was investigated by means of hydrogen breath analysis. Fructose absorption was quantified with lactulose standards. Significant hydrogen production (greater than or equal to 20 ppm rise of breath hydrogen) was found after challenge with 10% solutions of 50, 37.5, 25, 20, and 15 g fructose in eight, seven, five, four and one subjects, respectively. One subject showed malabsorption after a 10 g dose and possibly also 5 g fructose. In contrast, no malabsorption could be detected in any of the 10 subjects after ingestion of 100 g, 75 g, or 50 g sucrose or a mixture of 50 g glucose and 50 g fructose. After ingestion of mixtures of 50 g fructose +25 g glucose and 50 g fructose +12.5 g glucose malabsorption was present in three and seven subjects, respectively. Symptoms during all challenges were mild, or absent. It is concluded that in the healthy state the absorption capacity of fructose given alone ranges from less than 5 g to more than 50 g. The absorption capacity of fructose given as sucrose is much higher. Glucose stimulates fructose uptake in a dose dependent fashion. The possible existence of more than one intestinal transport system for fructose is considered. The elucidation of the clinical relevance of the findings is important.